Methodology Of Comparative Analysis Of Cars In Urban Conditions Using Information Technologies - Ziyayev Kamoliddin Zukhritdinovich; Abdujalilova M.B; Yangiyeva I.I (Global Scientific Publishing, 2024)
There are many methods in the world to reduce the fuel consumption of passenger cars, in most cases aimed at increasing the structural efficiency of the equipment. In real-life operating conditions, traditional methods for assessing modern passenger car designs need to be improved. One of the ways to solve the problem is to use mathematical models of the relevant processes using information technology. This article provides software for modeling the fuel efficiency of passenger cars during the driving cycle
Keywords: Passenger car; fuel efficiency; petroleum product